Comparative efficacy and safety of anticoagulants for prevention of venous thromboembolism after hip and knee arthroplasty: A network meta-analysis. (2nd November 2017) - Hur, Min; Park, Sun-Kyung; Koo, Chang-Hoon; Jung, Eun Dhong; Kang, Pyoyoon; Kim, Won Ho; Kim, Jin-Tae; Jung, Chul-Woo; Bahk, Jae-Hyon
Abstract : Background and purpose — New oral anticoagulants have been developed to prevent venous thromboembolism (VTE) after knee or hip arthroplasty. Although there have been several network meta-analyses (NMA) to compare different regimens, an NMA including 2 different enoxaparin doses and edoxaban has not been performed. Methods — Standard NMA for fondaparinux, dabigatran, rivaroxaban, apixaban, edoxaban, and enoxaparin was performed. Outcome variables included a composite of total VTE and major/clinically relevant bleeding. The rank probabilities of each treatment outcome were summarized by the surface under the cumulative ranking curve. Results — Fondaparinux, rivaroxaban, and apixaban were associated with a reduced risk of VTE compared with enoxaparin, while dabigatran was not. None of these 3 drugs increased bleeding compared with enoxaparin 30 mg twice daily. However, fondaparinux and rivaroxaban increased bleeding compared with enoxaparin 40 mg once daily, while apixaban did not. Apixaban was even associated with decreased major/clinically relevant bleeding compared with enoxaparin 30 mg twice daily or 40 mg once daily. When edoxaban was included in the NMA, edoxaban decreased VTE and did not increase bleeding compared with enoxaparin. Interpretation — A higher efficacy of fondaparinux and rivaroxaban compared with enoxaparin was associated with increased bleeding tendency, while apixaban was superior to enoxaparin regarding both efficacy and safety. A clustered ranking plot showed that apixaban might be the most preferred regarding efficacy and safety. However, our results were driven by indirect statistical inference and were limited by the heterogeneity of the bleeding outcome definitions, drug initiation and continuation, and different surgery types.